A Comparison Objective Refraction Results of Autorefractor and Non-Cyclopegic Retinoscope with Subjective at SDN 17 Kebon Jeruk - Warti, Dwi; Goenawan, Kristian; Silaen, Desi Hartati (Jurnal MedScientiae, 2025)
Refractive errors are the leading cause of visual impairment among school-aged children. Early detection is essential, particularly in children who have difficulty providing subjective responses. Objective refraction instruments, such as autorefractors and non-cycloplegic retinoscopes, can be used as alternatives. This study aimed to compare the objective refraction results obtained using an autorefractor and a non-cycloplegic retinoscope, and to determine which instrument provides results most closely aligned with subjective refraction. This cross-sectional study involved 196 students aged 7 to 12 years from SDN 17 Kebon Jeruk. Each participant underwent refractive examinations using all three methods. The spherical equivalent (SE) results were compared within a tolerance of ±0.25 diopters (D) and analyzed using the McNemar test. The findings showed that the non-cycloplegic retinoscope produced results significantly closer to subjective refraction (p < 0.001), with agreement rates of 83.7% in the right eye and 87.2% in the left eye. In comparison, the autorefractor showed agreement rates of 55.6% and 62.8%, respectively. The SE differences with the retinoscope were also smaller and more consistent. In conclusion, the non-cycloplegic retinoscope provides refractive values that are more comparable to subjective results than the autorefractor, making it a more recommended instrument for refractive screening in elementary school children.